Point defect determination by photoluminescence and capacitance-voltage characterization in a GaN terahertz Gunn diode - 李亮 杨林安 周小伟 张进成 郝跃 (Chinese physics B, 2013)
Photoluminescence （PL） measurement is used to study the point defect distribution in a GaN terahertz Gunn diode, which is able to the degrade high-field transport characteristic during further device operation. PL, secondary ion mass spectroscopy （SIMS）, transmission electron microscope （TEM）, and capacitance-voltage （C-V） measurements are used to discuss the origin of point defects responsible for the yellow luminescence in structures. The point defect densities of about 1011 cm-2 in structures are extracted by analysis of C-V characterization. After thermal annealing treatment, diminishments of point defect densities in structures are efficiently demonstrated by PL and C-V results.